Optimization of the primary nozzle for design a high entrainment ejector in spacesuit portable life support system. (25th November 2022) - Guo, Haowei; Wang, Chen; Wang, Lei
Highlights: High ventilation ratio ejector for the portable life support system was proposed. Effects of geometric parameters on the ejector performance were systematically studied. The optimum structure of high entrainment ratio ejector was obtained. Abstract: In looking forward to the future of human space exploration, it is increasingly stringent for the ventilation circuit subsystem in terms of reliability, simplicity and energy-efficient. Considering this requirement, the ejector, with the advantages of miniature size, no parasitic energy consumption and high reliability, is considered an appropriate alternative to the ventilation fan because it simultaneously implements the functions of mixing, entraining, and lifting pressure. This paper proposed a high entrainment ejector for application in spacesuit portable life support systems. The optimizations of the ejector nozzle geometrical parameters and nozzle exit position (NXP) were performed using a validated three-dimensional numerical model under various operating conditions. The results show that the NXP has a more significant effect on entrainment performance than other geometrical parameters in spacesuit portable life support systems, and the optimum NXP are not impacted by changes of the primary flow pressure and mixing chamber diameter, which similarly obtained the optimal entrainment ratio at the nozzle exit position of 2 mm. The maximum increments of entrainment ratio with the NXP varying from −4 mm to 8 mm are 0.2945 and 0.7664 under different primary flow pressures and mixing chamber diameters, respectively. Compared with the nozzle exit position, the most effects of nozzle converging angle and length on entrainment ratio are just 0.0864 and 0.0445. The optimum ejector extends the oxygen service duration by 12 min compared to the original one for the same volume of an oxygen tank, which is vital for the astronauts to conduct extravehicular activities in outer space.